EFFECTIVE USE OF INFORMATION AND INNOVATION TECHNOLOGY IN TEACHING FOREIGN LANGUAGE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides an insight into the innovations that are being implemented in various aspects of our lives thanks to the improvement of modern innovative techniques and technologies that are being created at a level that amazes a person today, their importance in the educational system that is being updated on the basis of the world andozes, the interaction of information technologies in education.